Ultraviolet radiation and water salinization on recirculating aquaculture systems - Gonçalves Junior, Lucas Pedro; Lara, Bernardo Santos; Carvalho, Samuel Alves de; Leal, Carlos Augusto Gomes; Miranda Filho, Kleber Campos; Figueiredo, Henrique César Pereira; Luz, Ronald Kennedy (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the effects of ultraviolet radiation (UV) and water salinity on nitrification, water quality, bacterial load, and juvenile tilapia growth in recirculating aquaculture systems (RASs). The experimental period was divided into two phases. The first one lasted 20 days and evaluated the effects of salinity (0 and 2 g L-1) and UV (with or without) on water quality during the period of substrate colonization by nitrifying bacteria. In the second phase, after the storage of juvenile tilapia, the effects of the same experimental factors were evaluated on water quality, bacterial load, and fish growth performance. The RASs employed were efficient for ammonia removal, regardless of the treatments used. During the experimental period, the nitrite concentrations increased linearly, with a more pronounced increase after fish storage until 30 days of the experiment. There were no significant effects of UV, salinity, or the interaction of both on total ammonia, nitrite, and alkalinity. The low levels of salinity (2 g L-1) and UV did not affect the nitrification process and fish performance. The use of UV is efficient to reduce the bacterial load of recirculating aquaculture systems.